Cover Image. (18th July 2022) - Cheng, Ke; Zhang, Jianghua; Yang, Shasha; Yin, Fawen; Li, Zixuan; Wang, Ting; Zhou, Dayong
Abstract : The cover image is based on the Research Article Acidolysis of phospholipids with medium‐chain fatty acids over M‐SBA‐15 (M = Zn, Al) silicas as efficient solid catalysts by Fawen Yin et al., https://doi.org/10.1002/jsfa.11832 . Abstract : The cover image is based on the Research Article Acidolysis of phospholipids with medium‐chain fatty acids over M‐SBA‐15 (M = Zn, Al) silicas as efficient solid catalysts by Fawen Yin et al., https://doi.org/10.1002/jsfa.11832 .